Cenário das outorgas de lançamento de esgoto concedidas em Belém-Pa - RODRIGUES, Suzana Teixeira (Universidade Federal do Pará, 2018)
Conditions of effluent disposal grants authorized by the Department of Environment and Sustainability (SEMAS) of the Municipality of Belém PA, Brazil, between 2013 and 2016, are analyzed. Current study is divided into three parts: (1) collection of data retrieved from the Department; (2) preparation of a map showing effluent disposal grant sites at present; (3) number of non-computerized effluent discharges for each urban water basin in the municipality of Belém. Results showed that there are 24 effluent water disposal grants in the municipality of Belém: 62.5% are effluent disposal grants to residential housing estates; 25% are effluent disposal grants for industries; 12.5% are effluent disposal grants for other sectors, including hospitals and airport. The water resource with the greatest number of disposal sites is the Igarapé/Canal de Val-de-Cans, with five effluent disposal grant sites, followed by Igarapé São Joaquim/São Raimundo, with four effluent disposal grant sites. Very few effluents are treated at tertiary level, with disinfection prior to release in the water body. In fact, most Treatment Stations lie at the secondary level, since only organic matter is removed. However, enterprises with septic tanks and filters are still extant. Results also demonstrate that the urban water basin with the greatest unaccountable effluent discharge is the Bacia do Una, with 44,680.32 m³/day, followed by the Bacia do Outeiro, with 28,567.20 m³/day. Data are the SEMAS´s official numbers and they do not reveal the true conditions of the water bodies. In fact, there are several other effluent discharges which have not been regulated by the department and which contribute towards unbridled pollution caused by sheer lack of a comprehensive sewerage system in the municipality of Belém.